A Comparative Study of Student Learning Motivation with Sevima Edlink and Google Classroom-Based Classroom Management - Anwar, Saepul; Wati, Desi Erna; Supriadi, Udin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Learning motivation is one of the factors that support the success of learning. However, in reality, many students are still not motivated, especially since the Covid-19 pandemic, so the use of the Learning Management System application in learning can be a solution. This research aims to: (1) Describe the level of student motivation using class management based on Sevima Edlink and Google Classroom. (2) Describe the comparison of class management based on Sevima Edlink and Google Classroom. This research uses a quantitative approach with a comparative method. The data collection is a closed questionnaire, and the analysis technique is descriptive and inferential. The results of this study indicate that: (1) Students’ learning motivation who use class management based on Sevima Edlink and Google Classroom has similarities, which is in the medium category. (2) There is a difference in the mean range between students' learning motivation using Sevima Edlink-based classroom management and Google Classroom. Still, the difference is not significant as indicated by the value of Sig. 2 tailed of 0.109 is greater than 0.025.